Modernism's Metronome : Meter and Twentieth-Century Poetics - Glaser, Ben (Book collections on Project MUSE., 2020)
"The author offers a historical account of modernist poetic form and analyzes how poetry was read and written in the twentieth century. The rise of free verse in the early 1900s is commonly thought to be a resistance to or liberation from regimented meter, privileging instead an element of "rhythm," but the author reads a range of modernist poetry in relation to the historical practice of metrical form"--